2010
DOI: 10.1186/1471-2288-10-68
|View full text |Cite
|
Sign up to set email alerts
|

A life-course and time perspective on the construct validity of psychological distress in women and men. Measurement invariance of the K6 across gender

Abstract: BackgroundPsychological distress is a widespread indicator of mental health and mental illness in research and clinical settings. A recurrent finding from epidemiological studies and population surveys is that women report a higher mean level and a higher prevalence of psychological distress than men. These differences may reflect, to some extent, cultural norms associated with the expression of distress in women and men. Assuming that these norms differ across age groups and that they evolve over time, one wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 57 publications
8
101
1
5
Order By: Relevance
“…Several studies showed no substantial bias for the K10 in relation to gender, education (Baillie 2005) or age (OConnor and Parslow 2010). The K6 also achieves an adequate level of measurement invariance across gender and age groups and over a 12-year period (Drapeau et al 2010). The K6 was validated with teens ).…”
Section: The Kessler Scalesmentioning
confidence: 99%
“…Several studies showed no substantial bias for the K10 in relation to gender, education (Baillie 2005) or age (OConnor and Parslow 2010). The K6 also achieves an adequate level of measurement invariance across gender and age groups and over a 12-year period (Drapeau et al 2010). The K6 was validated with teens ).…”
Section: The Kessler Scalesmentioning
confidence: 99%
“…The K6 measure was developed specifically for use in population-based surveys, 24,25 it has been validated on populations in the United States and around the world as a measure of psychological distress, and it is used in many population-based surveys to estimate the public health effects and prevalence of mental illness. 4,[24][25][26][27][28][29][30][31][32][33] While measures of psychological distress do not identify a specific mental illness, it is most closely associated with mood and anxiety disorders, and increasing levels are associated with increased symptom severity 2 and a higher likelihood of mental illness. 3 The K6 asks about the frequency of six symptoms: "During the past 30 days, how often did you feel .…”
Section: Study Protocolmentioning
confidence: 99%
“…The K10 (and it's six item abbreviated version, the K6), is a well validated instrument used to screen for psychological distress in large, epidemiological surveys (R. C. Kessler et al, 2003). It has been administered in annual government health surveys in the United States, Canada, and Australia (Drapeau et al, 2010;Furukawa, Kessler, Slade, & Andrews, 2003;Kessler et al, 2002) and is also used by the World Health Organization in their World Mental Health Surveys (Kessler et al, 2010). The scale consists of 10 questions regarding level of psychological distress experienced in the past four weeks.…”
Section: Methodsmentioning
confidence: 99%